FUNGSI UNGKAPAN TRADISIONAL PADA PERIBAHASA KUTAI - Indah Sari Lubis; Fatimah M (Universitas Singaperbangsa Karawang, 2020)
Kutai language as one of the local languages in East Borneo, was necessarily maintained from generation to generation. The effort of maintaining language has been variously applied through the lens of local wisdom existed in culturally product. Proverb is the culture product of Kutai Kartanegara. There are many moral messages contained in Kutai Kartangera proverbs. This study examines the functions of traditional utterances of Kutai Kartanegara within descriptive qualitative method. The theory of Traditional Utterance Function by Danandjaya was used in the study. The library approach was applied to collect the data. The study was expected to contribute the horizon, to improve the references correlating to the function of traditional utterances particularly in Kutai Kartanegara proverbs and to be the references to the other researchers who were relevance to the study. The result showed that the functions of traditional utterances on Kutai proverbs were the four functions of traditional utterances namely the functions of education, individual ethical value, moral and social respectively